2011
DOI: 10.1111/j.1440-1754.2011.02242.x
|View full text |Cite
|
Sign up to set email alerts
|

Practitioner characteristics and the treatment of children and adolescents with attention deficit hyperactivity disorder

Abstract: There are significant differences in prescribing practice between paediatricians and psychiatrists. These variations may reflect differing training programs and patient populations, and merit close consideration in any review arising from the publication of the recent NHMRC guideline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Similarly, in Australia, psychiatrists were more likely than pediatricians to treat patients with multiple psychotropic medications and to prescribe higher stimulant doses (Preen, Calver, Sanfilippo, Bulsara, & Holman, ). Also, psychiatrists were more likely to use stimulants as first‐line treatments whereas pediatricians were more likely to consider prescribing for children aged 4 years and younger (Mitchell et al, ). On the contrary, a US study showed that psychiatrists were 42% less likely than primary care physicians to treat patients with ADHD medication (Chen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in Australia, psychiatrists were more likely than pediatricians to treat patients with multiple psychotropic medications and to prescribe higher stimulant doses (Preen, Calver, Sanfilippo, Bulsara, & Holman, ). Also, psychiatrists were more likely to use stimulants as first‐line treatments whereas pediatricians were more likely to consider prescribing for children aged 4 years and younger (Mitchell et al, ). On the contrary, a US study showed that psychiatrists were 42% less likely than primary care physicians to treat patients with ADHD medication (Chen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…There is still a wide range of variation in adherence of clinical practice to available guidelines among various healthcare paediatric professionals involved in managing children with ADHD and across various locations [24][25][26]. There are clear indications and scope for improvement of clinicians' adherence to existing guidelines [27].…”
Section: Clinical Care Pathwaysmentioning
confidence: 99%
“…Although rates vary geographically, international and local studies have shown that rates of psychotropic medication prescribing to children with DB/MH problems are increasing. [1][2][3][4] Longitudinal Study of Australian Children data from 2012 to 2015 showed that psychotropic medications were the second most commonly dispensed medication group comprising 18.7% of all prescriptions dispensed for [8][9][10][11][12][13][14][15][16] year olds. 5 Audits from 2008 and 2013 of Australian general paediatricians conducted by the Australian Paediatric…”
mentioning
confidence: 99%
“…9,10 Reasons for this may include individual patient factors (such as age, co-morbidities and access to insurance) and provider factors. [11][12][13][14] A 2008 UK study concluded that although the majority of paediatricians felt knowledgeable about the licensed usage and side effect profiles of psychotropic medications, few felt sufficiently competent in prescribing these medications. 15 During advanced general paediatric training in Australia and New Zealand, psychotropic prescribing is currently a learning objective, but not directly assessed.…”
mentioning
confidence: 99%